Severe chickenpox disease and seroprevalence in Sweden – implications for general vaccination. (October 2021) - Widgren, K; Persson Berg, L; Mörner, A; Lindquist, L; Tegnell, A; Giesecke, J; Studahl, M
Highlights: The majority of hospitalized chickenpox patients had complications. Half of all chickenpox complications was seen in previously healthy children. Adult migrants had an increased risk of chickenpox hospitalization. The varicella zoster IgG seroprevalence was 66.7% at 5 years and 91.5% at 12 years. Abstract: Objectives: To describe the current panorama of severe chickenpox disease and seroprevalence in Sweden, as a basis for the approaching decision on universal vaccination. Methods: Patients discharged with an International Classification of Diseases 10th revision-code for chickenpox (B01-B01.9) in eight pediatric and infectious diseases departments in Stockholm and Gothenburg in 2012-2014 were included in the study and their medical charts were reviewed. Further, residual serum samples collected from 11 laboratories across Sweden were analyzed for varicella zoster IgG-antibodies to investigate age-specific seroprevalence. Results: A total of 218 children and 46 adults were included in this hospital-based study; 87.2% of children and 63.0% of adults had complications. An underlying condition was not associated with an increased risk of complication. Dehydration (31.7%), bacterial skin infections (29.8%) and neurological involvement (20.6%) were the most frequent complications in children. Among adult cases, 63% were born abroad. The seroepidemiological analysis included 957 patient samples. Seroprevalence was 66.7% at 5 years and 91.5% at 12 years. Infants and adolescents/adults were overrepresented among admitted patients compared to seroprevalence data. Conclusions: Half of all complications in hospitalized chickenpox cases were seen in previously healthy children, which supports universal childhood vaccination. Adult migrants was a risk group for chickenpox hospitalization. Age-specific seroprevalence was similar to neighboring countries.